2012
DOI: 10.3329/bjz.v40i1.12897
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Quality of Marketed Mola Fish, Amblypharyngodon Mola From Dhaka Metropolis

Abstract: The bacteriological quality of mola fish (Amblypharyngodon mola) from three local fish markets as fresh and as frozen from three departmental chain shops of Dhaka metropolis were analyzed. The microbial quality parameters varied with different sources and the quality was found to be poor for local market fish samples. In total 24 samples were considered for bacteriological quality analysis and 10 pathogenic isolates for antibiotic sensitivity test to 12 antibiotics. The total bacterial count ranged from 1.8 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 14 publications
1
22
0
Order By: Relevance
“…Nilla et al (2012b) found TCC 2.4 ± 0.30 × 10 3 to 8.0 ± 0.55 × 10 4 cfu/g in A. mola from Dhaka metropolis local markets whereas Begum et al (2010) found highest TC >240 mpn/g in local marketed B. sarana. On the contrary, Zahid et al (2011) did not found TCC in normal P. sarana from local markets.…”
Section: Nutrient Compositionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nilla et al (2012b) found TCC 2.4 ± 0.30 × 10 3 to 8.0 ± 0.55 × 10 4 cfu/g in A. mola from Dhaka metropolis local markets whereas Begum et al (2010) found highest TC >240 mpn/g in local marketed B. sarana. On the contrary, Zahid et al (2011) did not found TCC in normal P. sarana from local markets.…”
Section: Nutrient Compositionmentioning
confidence: 99%
“…The present findings are supported by some previous works of different scientists who worked on punti and small fish. Nilla et al (2012b) found TBC ranged between 1.8 ± 0.25 × 10 4 to 6.5 ± 0.75 × 10 6 cfu/g in mola fish (Amblypharyngodon mola) from local markets of Dhaka metropolis where the whole fish was considered for bacterial quality analysis. Begum et al (2010) found TVBC (total viable bacterial counts) 3.3 × 10 5 to 1.9 × 10 8 cfu/g in sarpunti (Puntius sarana) collected from local markets.…”
Section: Nutrient Compositionmentioning
confidence: 99%
See 3 more Smart Citations